Milk Siblings Tracing System for Malaysians - Siti Fatimah A. RAZAK; Noor Hisham KAMIS; Mohd. Fikri Azli ABDULLAH; Nur Liyana ROSLI (Communications of International Proceedings, 2022)
Non-maternal nursing forms a milk kinship which refers to interpersonal relations regulating marriages and interactions with the opposite sex is formed among them once there is a completion of five breastfeeding sessions at different period. However, authorities in many countries have not fully established any enactment or processes to properly store information related to the milk siblings, biological parents, close relatives etc. Hence, this study aims to mitigate the unfortunate situation by utilising the information technology which allows Muslim couples to pre-screen their milk kinship status prior to the solemnization stage. A database which stores the details of the breastfed child, biological parents, siblings is developed based on the milk Mahramiyat or kinship rules. Users may interact with the database by recording their details and submitting queries via the user interface which is accessible via online site and mobile application. A milk siblings tracing system is proposed to be used as a precautionary system for future bride and groom in addition to currently imposed pre-marital health screening in which couples that are going to get married are tested for genetic, infectious and blood transmitted diseases to prevent any risk of transmitting any disease to their children. Comparative to the pre-marital health screening often required when couples submit their wedding registration, the tracing system may also serve as a guide for the authorities to approve or not approve Muslims marital applications in accordance with the milk Mahramiyat rules.
Keywords: Milk kinship; Breastfeeding; Non-maternal; Ar-Radhaah; Human milk bank